Internal audit and its role in assuring an effective corporate governance implementation: A theoretical analysis. - Med Lebrague, Riad; Chelil, Abdellatif; Meziane, Tadj (Finance and Business Economies Review, 2019)
Corporate governance gained a significant interest form academics and practitioners in business environment, in the last two decades or so. The misrepresentation of companies’ financial reports and performance had a sever negative consequences, not just of what it caused to investors’ funds and employees layoffs but also to country’s economy in general. As a result, governments and related economic authorities presented laws and mechanisms (including internal audit) that should prevent such consequences. This paper aims to analyse theoretically the role of internal audit function that support and deliver a better corporate governance. It includes also discussing the auditors function and the audit committee impact and governance over company’s management.